Time-Course Transcriptome Analysis of Arabidopsis Siliques Discloses Genes Essential for Fruit Development and Maturation. Issue 3 (1st October 2018) - Mizzotti, Chiara; Rotasperti, Lisa; Moretto, Marco; Tadini, Luca; Resentini, Francesca; Galliani, Bianca M.; Galbiati, Massimo; Engelen, Kristof; Pesaresi, Paolo; Masiero, Simona
Abstract : Dynamic changes in the transcriptome of developing seedless fruits reveals key regulators of fruit growth and maturation. Abstract: Fruits protect the developing seeds of angiosperms and actively contribute to seed dispersion. Furthermore, fruit and seed development are highly synchronized and require exchange of information between the mother plant and the developing generations. To explore the mechanisms controlling fruit formation and maturation, we performed a transcriptomic analysis on the valve tissue of the Arabidopsis ( Arabidopsis thaliana ) silique using RNA sequencing. In doing so, we have generated a data set of differentially regulated genes that will help to elucidate the molecular mechanisms that underpin the initial phase of fruit growth and, subsequently, trigger fruit maturation. The robustness of our data set has been tested by functional genomic studies. Using a reverse genetics approach, we selected 10 differentially expressed genes and explored the consequences of their disruption for both silique growth and senescence. We found that genes contained in our data set play essential roles in different stages of silique development and maturation, indicating that our transcriptome-based gene list is a powerful tool for the elucidation of the molecular mechanisms controlling fruit formation in Arabidopsis.